Machine Learning-Based Score Prediction for IPL Matches: A Comprehensive Analytical Approach - Mahto, Shankarprasad; Gupta, Pawan (Journal of Advanced Research in Applied Artificial Intelligence and Neural Network, 2025)
Cricket is not just a sport but a blend of strategic planning and on-field performance. The Indian Premier League (IPL), being one of the most celebrated cricket leagues globally, attracts immense attention from fans, analysts, and stakeholders. This research focuses on developing a machine learning-based predictive model for forecasting IPL match scores. By analysing historical data, team compositions, player statistics, and environmental factors, the study presents a systematic approach to creating accurate predictions. The model's effectiveness is evaluated using various machine learning algorithms, making this study a stepping stone for sports analytics.